Creative territories and improving local cultural identity (Desenvolvimento em Questão, 2025)
This article seeks to trace the relationship between the implementation of creative and cultural territories, in their various typologies, such as creative and cultural districts, clusters, hubs, ecosystems and quarters, and their impact on local cultural identity. In order to achieve this objective, an integrative review was conducted using data collected from international databases, Scopus, Web of Science and Ebsco, which made it possible to verify the existence of benefits and negative impacts on local cultural identity from creative and cultural territories. The study was also able to ascertain what activities territories need to carry out in order to strengthen and preserve their respective cultural identity.
Keywords: Creative economy; Cultural economy; Creative ecosystem; Creative and cultural territories; Urban planning